PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI KELAS IX SMPN 22 PADANG - Kamelina, Irhamiyah Kemil (Jurnal Edukasi dan Penelitian Matematika, 2023)
Understanding of Mathematical concept is one of  objectives of mathematics learning that must be achieved by student. But in reality, several previous researches have shown that understanding of mathematical concept of students is still low. This also happen to students in class IX SMPN 22 Padang. Student Teams Achievement Division choosen to solve that problem. The research methodology used is Quasy Implement the Posttest Only Non-equivalent Group Design in your research experiments. The P-value obtained from the analysis of the mathematical concept understanding test at a significance level of ?=0.05 was 0.000. Since a P-value below ? would indicate rejection, ?-0 was accepted. This finding indicates that students in Class IX SMPN 22 Padang who study mathematical concepts using the Student Teams Achievement Division cooperative learning model have a greater grasp of those concepts than those who learn using traditional learning methods..Keywords – Conventional Learning, Student Teams Achievement Division, Understanding of Mathematical Concept